Implementasi Pembelajaran Berdiferensiasi dalam Kurikulum Merdeka untuk Meningkatkan Partisipasi Aktif Siswa di Sekolah Dasar Inklusi - Denri Laurensius Sitanggang; Sandy Anugrah Siburian; Anatasia Egrisia Saragi; Asna Istikmalatul Muktamaroh; Gilang Fathir Andikha; Alia fatia Zahra olii (Jurnal Keluarga Sehat Sejahtera, 2026)
Differentiated learning is one of the relevant approaches in the implementation of the Merdeka Curriculum because it is able to accommodate the diverse learning needs of students, especially in inclusive elementary schools. This study aims to analyze the implementation of differentiated learning in the Merdeka Curriculum and its role in improving students’ active participation in inclusive elementary schools. This study employed a qualitative approach using a library research method. Data sources were obtained from scientific journals, books, and relevant educational documents related to the research topic. Data were collected through documentation studies and analyzed using descriptive qualitative analysis through data reduction, data presentation, and conclusion drawing. The results of the study indicate that differentiated learning is capable of creating a more flexible, adaptive, and student-centered learning process through content, process, and product differentiation. This approach has been proven to increase students’ engagement and active participation, including students with special needs, because learning activities are adjusted to students’ readiness, interests, and learning styles. However, its implementation still faces several challenges, such as limited teacher understanding, learning media, and heterogeneous classroom conditions. Therefore, improving teacher competence and strengthening school support are necessary to optimize the implementation of differentiated learning in creating inclusive and meaningful learning environments.